The Sources and Resources of Our Indigenous Theology: An Australian Aboriginal Perspective - Parkin, Evelyn (The ecumenical review, 2010)
I will attempt to show the Australian Aboriginal Christian from the spiritual, physical and cultural perspectives. The point that I wish to highlight is that there is an expression of continuity of relationship and ritual sacredness between my ancient people and their Higher Power (known by various names). This relationship is an unbroken thread that has weaved its way through the passages of time. It has been passed on for thousands of years to us here today as Aboriginal Christians. We are not only the “Children of God,” but are also the “Children of the Dreaming”– this is my identity.